ANALISIS PEMBAYARAN PREMI DALAM ASURANSI SYARIAH - Agus Purnomo (al-Uqud : Journal of Islamic Economics, 2017)
The purpose of this study to analyze the model of calculating rates of the premium insurance on savings and non-savings products to segmentation market and the profit. The method of this study used the descriptive qualitative.Related to characteristics of the product for saving products more appropriate to applied to individu segmentation, whereas the non-saving product more appropriate if marketed to groups or companies. Companies that invest on high rate of return will use a relatively of smaller debt. The high rate of return will allow them to fund the majority of the finance when they need with the funds that obtained from internal activities.